Uptake of case management intervention for continuity of HIV treatment among released inmates in South Africa - Ndini, Pretty (My University, 2020)
Background: Globally, South Africa has one of the highest inmate rates and one of the largest Human Immunodeficiency Virus (HIV) epidemics. Over the years, there have been improvements in accessibility to HIV treatment for incarcerated inmates within correctional facilities in South Africa, with many inmates initiating antiretroviral therapy (ART) and achieving virologic suppression. However, there are no effective referral systems to facilitate linkage to ART clinics in the general community after release from correctional centres. In this study, we sought to evaluate the uptake of an individualised case management intervention designed to facilitate post-release linkage to HIV care services among inmates released on ART. Methods: This is a secondary data analysis of a prospective cohort of released HIV-positive inmates enrolled in the I-Thuba Linkage-to-Care study conducted in Gauteng Province of South Africa. Briefly, 192 participants who were assigned to receive case management support as an intervention to facilitate linkage-to-care and released from January 2016 to March 2017 were included in this analysis. After excluding participants who died and those re-incarcerated, we remained with a sample size of 188 participants in the final analysis. We assessed factors associated with uptake of case management support (i.e. attending at least one of the three available case management sessions) using univariable and multivariable logistic regression methods. Further, using the simple logistic regression, we assessed the association between uptake of case management support and 90-day linkage to HIV care after release from the correctional centre. Results: Of the 188 participants assigned to receive case management support, 71% (n = 133) attended at least one case management session, either in-person or telephonically. Uptake of case management was associated with being released on parole and disclosure of HIV status. In this study, participants who had completed their sentences (non-parolees) were less likely to utilise case management support than inmates who were released under supervision (Adjusted Odds Ratio (AOR) = 0.24, 95% Confidence Interval (CI): 0.11 - 0.52). Also, participants who reported having disclosed their HIV status were more likely to attend case management sessions than those who did not disclose their HIV status (AOR = 5.06, 95% CI: 2.16 - 11.84). Utilization of the case management support was associated with improved linkage-to-care compared to non-utilization of the case management intervention (AOR = 5.62; 95% CI: 2.25 - 14.03). Conclusion: Our study findings suggest that case management can be successfully implemented in the South African setting and may reduce ART disruption in the period immediately following release. Further research is required to identify methods to increase the reach of case management support to individuals who have completed their sentences and are not required to remain in contact with the corrections system after release. In addition, there is value in strengthening pre-release programmes to provide disclosure counselling as this may influence how individuals engage with HIV care support services after release
A research report submitted in fulfilment of the requirements for the of Master of Science in the field of Epidemiology and Biostatistics to the Faculty of Science, University of Witwatersrand, Johannesburg, 2020